THE ROLE OF HUMAN RESOURCES IN BUILDING A SUSTAINABLE AND RESPONSIBLE CORPORATE CULTURE - Fadlika; Leolita, Yourieke Estherina; Yusda, Desi Derina; Nugroho, Yudhinanto Cahyo; WA, Armalia Reny (Fakultas Ekonomi Universitas Djuanda, 2024)
This research aims to examine the influence of HR practices on corporate culture, with sustainability practices and social responsibility as intervening variables at Puskesmas Balik Bukit Lampung Barat. Utilizing a total sampling technique, data was collected from 52 employees through an online questionnaire and analyzed using Smart PLS. The results indicate that HR practices have a strong positive effect on both sustainability practices and social responsibility. Furthermore, sustainability practices significantly influence corporate culture and act as a mediator between HR practices and corporate culture, while social responsibility does not show a significant direct or mediating effect. The findings highlight the crucial role of HR practices in fostering sustainability, which in turn shapes the corporate culture. This study provides valuable insights for healthcare organizations to improve their corporate culture and service delivery through strategic HR practices focused on sustainability and social responsibility. ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh praktik SDM terhadap budaya perusahaan, dengan praktik keberlanjutan dan tanggung jawab sosial sebagai variabel intervening di Puskesmas Balik Bukit Lampung Barat. Dengan menggunakan teknik total sampling, data dikumpulkan dari 52 karyawan melalui kuesioner online dan dianalisis menggunakan Smart PLS. Hasil penelitian menunjukkan bahwa praktik SDM memiliki pengaruh positif yang kuat terhadap praktik keberlanjutan dan tanggung jawab sosial. Lebih lanjut, praktik keberlanjutan secara signifikan mempengaruhi budaya perusahaan dan bertindak sebagai mediator antara praktik SDM dan budaya perusahaan, sementara tanggung jawab sosial tidak menunjukkan efek langsung atau mediasi yang signifikan. Temuan ini menyoroti peran penting praktik SDM dalam mendorong keberlanjutan, yang pada gilirannya membentuk budaya perusahaan. Studi ini memberikan wawasan yang berharga bagi organisasi layanan kesehatan untuk meningkatkan budaya perusahaan dan penyediaan layanan mereka melalui praktik-praktik SDM strategis yang berfokus pada keberlanjutan dan tanggung jawab sosial.